Presentation and surgical management of a patient with a true cleft mandible - Nikita R. Shah; David M. McGoldrick; Ian Sharp (Elsevier, 2022)
Clefts involving the mandible and lower lip are very rare, with less than 80 cases having been reported worldwide. The objective of this case report is to highlight this unusual type of facial cleft, and to present the principle features and management typically associated with it. We carefully describe our surgical planning and management of the patient alongside a compilation and comparison of different surgical techniques described in the literature thus far. In this report, we discuss a patient with a cleft of the lower lip, true cleft mandible with independent movements of his mandibular segments, ankyloglossia, and a fistula extending from the mandible to the suprasternal notch complicated with congenital heart abnormalities. We explore the different approaches of when to close the hard and soft tissues, however, there is still no clear surgical protocol for treating cleft mandibles but with more cases and their management and outcomes being reported, this is something which will be useful to develop.